Rapid detection reagent for oil quality, preparation method of rapid detection reagent, kit and detection method of kit

By using a composite material of copper-polyphenol nanospheres outsourcing silver nanoparticles as a Raman-reinforced substrate and combining 3-MBA beacon molecules, the problems of poor substrate stability and uneven signal enhancement in the prior art are solved, and the problem of correctness and uneven signal enhancement is achieved. Rapid and accurate detection of propyl gallate in oils.

CN119438169APending Publication Date: 2025-02-14XIAMEN HUAXIA UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411348018.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing Raman spectroscopy technology has problems such as poor substrate stability and uneven signal enhancement in oil antioxidant detection, resulting in insufficient detection accuracy.

Method used

A composite material with copper-polyphenol nanospheres outsourced silver nanoparticles (Cu-TA@Ag) was used as the Raman-reinforced substrate, and 3-mercaptobenzeneboric acid (3-MBA) was used as the beacon molecule to form a rapid detection reagent.

Benefits of technology

It realizes rapid and accurate detection of propyl gallate in oil products, improves the sensitivity and specificity of detection, and is simple in preparation and is easy to promote.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438169A_ABST
    Figure CN119438169A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of oil product antioxidant detection, and provides an oil product quality rapid detection reagent, the oil product quality rapid detection reagent comprises a composite nanometer material and beacon molecules, the composite nanometer material is a composite material shell structure formed by coating silver nanoparticles (Cu-TA-Ag) on copper-polyphenol nanospheres, the beacon molecule is a core-shell nano material of 3-mercaptophenylboronic acid (3-MBA). On the basis, enhancement of Raman signals can be realized, so that rapid trace detection of oil quality can be realized, and the detection accuracy is improved. In addition, the invention further provides a preparation method of the rapid detection reagent for the oil quality, a kit and a detection method of the kit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of oil antioxidant detection, and in particular to a rapid detection reagent for oil quality and a preparation method thereof, a kit, and a kit detection method. Background Art

[0002] Propyl gallate (PG), 3,4,5-trihydroxybenzoic acid propyl ester, is one of the most widely used phenolic antioxidants due to its high temperature resistance and antioxidant properties, and has strong reducing properties. Generally speaking, propyl gallate is often added to edible oils to prevent excessive oxidation of the oil. However, excessive use of propyl gallate can cause lipid peroxidation in food, leading to acidification and the generation of free radicals. The lipid peroxidation process is accompanied by the production of low molecular weight fatty acids such as aldehydes and ketones, which have adverse effects on nutritional value and health. Therefore, more organizations such as the European Union, the United States and the Food Safety Bureau of China (GB-2760-2011) have proposed that the maximum allowable amount of propyl gallate in edible oils is 0.1g / kg. Therefore, monitoring the content of antioxidants in oil products and maintaining the oxidation state of lipids in food are essential to maintaining human health.

[0003] Raman spectroscopy technology has shown great potential in the field of food safety testing due to its non-destructive, high sensitivity and rapid analysis. For the detection of antioxidants such as propyl gallate, Raman spectroscopy can directly provide molecular vibration information, and can achieve rapid and accurate quantitative analysis without sample pretreatment or complex separation steps. However, existing substrates have great limitations. For example, metals (such as Au, Ag, Pt) and semiconductor substrates perform well in Raman signal enhancement, but their poor stability and uneven distribution of metal particles limit their widespread promotion in practical applications, and lead to insufficient accuracy of detection reagents for oil quality.

[0004] Therefore, the present application studies a rapid detection reagent for oil quality, which has a more efficient and accurate Raman enhanced substrate material, making the detection more precise and easy to promote and use. Summary of the invention

[0005] In order to obtain a more efficient and accurate Raman enhanced substrate material, so that the detection is more precise and easy to promote and use.

[0006] On the one hand, the present application provides a rapid detection reagent for oil quality, which adopts the following technical solution:

[0007] A rapid detection reagent for oil quality comprises a composite nanomaterial and a beacon molecule. The composite nanomaterial is a composite shell structure of copper-polyphenol nanospheres encapsulating silver nanoparticles (Cu-TA@Ag), and the beacon molecule is a core-shell nanomaterial of 3-mercaptophenylboronic acid (3-MBA).

[0008] On the other hand, the present application provides a method for preparing a rapid detection reagent for oil quality, which adopts the following technical solution:

[0009] A method for preparing a rapid oil quality detection reagent is prepared using the above-mentioned rapid oil quality detection reagent, comprising the following steps:

[0010] S11, preparation of copper polyphenol nanosol (Cu-TA): polyether F127 is dissolved in a mixed solution (containing ethanol, water and ammonia), stirred, and then tannic acid (TA) is added, and then formaldehyde solution is added for reaction, and then copper nitrate solution is added; the obtained solution is heated and then cooled to room temperature, and centrifuged to obtain copper-polyphenol nanosol;

[0011] S12, preparation of composite nanomaterial (Cu-TA@Ag): after diluting the copper polyphenol nanosol, slowly adding the silver ammonia solution to react to obtain a composite nanomaterial;

[0012] S13. Preparation of a rapid detection reagent for oil quality: Cu-TA@Ag solution and 3-MBA are added to a centrifuge tube and mixed evenly. The centrifuge tube is sealed and incubated at room temperature to obtain a rapid detection reagent for oil quality.

[0013] Optionally, in step S11: the mass of the polyether F127 is 0.1-0.3g; the mixed solution is prepared according to the following proportions: the volume of ethanol is 8-10ml, the volume of ultrapure water is 30-50ml, the volume of ammonia solution is 0.1-0.5mL, and the stirring time is 30-60min; the volume of tannic acid (TA) is 4-5mL, the mass fraction of the formaldehyde solution is 3.7wt%, the volume of the formaldehyde solution is 4-5mL, and the reaction time is 12-24h; the concentration of the copper nitrate solution is 80-100mg / mL, the volume of the copper nitrate solution is 1-2mL, the solution heating temperature is 80-100℃, and the heating time is 10-12h; the centrifugal speed is 7000rpm, and the centrifugal time is 10min.

[0014] Optionally, in step S12, the volume of the copper polyphenol nanosol after dilution is 30 mL, the addition rate of the silver ammonia solution is 100-300 μL / min, the concentration of the silver ammonia solution is 10-30 mg / mL, the volume of the silver ammonia solution is 10-20 mL, and the solution reaction time is 20-50 min.

[0015] Optionally, in step S13, the volume of the composite nanomaterial solution is 0.5-1.5 mL, the volume of the 3-MBA solution is 50-150 μL, the concentration is 0.5-1 mm, the centrifuge tube is 2 mL, and the incubation time is 5-8 h.

[0016] On the other hand, the present application provides a kit, which adopts the following technical solution:

[0017] A kit comprises the above-mentioned rapid oil quality detection reagent and a methanol solution, wherein the methanol solution is used for extracting propyl gallate in the oil.

[0018] On the other hand, the present application provides a kit detection method, which adopts the following technical solution:

[0019] A kit detection method comprises the following steps:

[0020] S21, mixing the above-mentioned kit and the sample to be tested evenly, and performing ultrasonic treatment;

[0021] S22. Quantitatively transfer the extract after ultrasonication to a centrifuge tube for centrifugation, and measure it using a Raman spectrometer; measure each sample solution three times and take the average value.

[0022] Optionally, in step S21: the volume of the sample to be tested is 1-2 mL, the volume of the methanol solution is 1-2 mL, and the ultrasonic time is 20-30 min.

[0023] Optionally, in step S22: the capacity of the centrifuge tube is 10 to 25 mL, the centrifugal speed is 3000 to 5000 rpm, and the centrifugal time is 3 to 5 min.

[0024] Optionally, in step S22, the measurement conditions of the Raman spectrometer are: the laser wavelength is 585-785 nm, the laser power is 30-50 mW, and the signal integration time is 1-5 s.

[0025] In summary, the present application includes at least one of the following beneficial technical effects:

[0026] 1. The rapid detection reagent of the present invention is used, and 3-MBA is used as a ligand to quantitatively detect propyl gallate in oil products. After the propyl gallate in the oil products is combined with the rapid detection reagent, the Raman signal is enhanced, thereby realizing rapid trace detection of the oil product quality and improving the detection accuracy;

[0027] 2. The preparation process of the rapid detection reagent of the present invention does not require ultra-high temperature or ultra-low temperature environment, and the operation is convenient;

[0028] 3. Surface enhanced Raman scattering (SERS) has multiple target fingerprint information in Raman spectra, has the potential for rapid, multi-dimensional analysis, and has good sensitivity and high specificity. Therefore, the present invention uses SERS to analyze the antioxidant propyl gallate in oil products, and creates an efficient and accurate antioxidant detection system, which is of great significance and has broad application prospects for the rapid detection of oil quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the synthesis of nanoparticles in performance test 1 of the embodiment of the present application;

[0030] Figure 2 is a scanning electron microscope image of the nanoparticles in performance test 1 of the embodiment of the present application;

[0031] Figure 3 is a transmission electron microscope image of the nanoparticles in performance test 1 of the embodiment of the present application;

[0032] Figure 4 is the STEM-EDS element mapping diagram of the nanoparticles in the performance test 1 of the embodiment of the present application;

[0033] Figure 5 It is the ultraviolet visible absorption spectrum (UV-vis) diagram in performance test 1 of the embodiment of the present application (the abscissa is the ultraviolet spectrum wave number, and the ordinate is the ultraviolet spectrum absorbance);

[0034] Figure 6 is the electron diffraction (SAED) pattern of the nanoparticles in performance test 1 of the embodiment of the present application;

[0035] Figure 7 is a graph of the particle size of the nanoparticles in performance test 1 of the embodiment of the present application;

[0036] Figure 8 is the zeta potential diagram of the nanoparticles in performance test 1 of the embodiment of the present application;

[0037] Fig. 9 It is the Fourier near infrared spectrum (FTIR) in performance test 2 of the embodiment of the present application (the abscissa is the infrared spectrum wave number, and the ordinate is the infrared spectrum absorbance);

[0038] Fig.10 It is the X-ray photoelectron energy spectrum in performance test 2 of the embodiment of the present application (the abscissa is the X-ray diffraction bonding energy, and the ordinate is the spectral score);

[0039] Fig.11 This is the mechanism for detecting Cu-TA@Ag simulated peroxidase in performance test 3 of the embodiment of the present application;

[0040] Fig.12It is the UV-visible absorption intensity curve of different systems in performance test 3 of the embodiment of the present application (the abscissa is the UV spectrum wave number, and the ordinate is the UV spectrum absorbance);

[0041] Fig.13 It is the Cu-TA@Ag in the performance test 3 of the embodiment of the present application. - EPR spectra of different radical adducts in catalytic H2O2 reactions;

[0042] Fig.14 It is the EPR spectra of different H2O2 concentrations in performance test 3 of the embodiment of the present application;

[0043] Fig.15 is the EPR spectra of different ABTS concentrations in performance test 3 of the present embodiment;

[0044] Fig.16 It is the surface enhanced Raman spectroscopy (SERS) in performance test 4 of the embodiment of the present application (the abscissa is the Raman spectrum wave number, and the ordinate is the Raman spectrum absorbance);

[0045] Fig.17 It is the surface enhanced Raman spectroscopy (SERS) in performance test 5 of the embodiment of the present application (the abscissa is the Raman spectrum wavenumber, and the ordinate is the Raman spectrum absorbance);

[0046] Fig.18 is the fitting curve of the surface enhanced Raman signal intensity in performance test 6 of the embodiment of the present application;

[0047] Fig.19 is a bar graph of the surface enhanced Raman signal intensity in performance test 7 of the embodiment of the present application;

[0048] Fig. 20 is a bar graph of the surface enhanced Raman signal intensity in performance test 8 of the embodiment of the present application;

[0049] Fig.21 It is the specific response diagram in performance test 9 of the embodiment of the present application. DETAILED DESCRIPTION

[0050] The following is combined with Figure 1-21 This application is described in further detail.

[0051] Embodiment 1:

[0052] The first embodiment of the present application discloses a rapid detection reagent for oil quality. The rapid detection reagent for oil quality comprises a composite nanomaterial and a beacon molecule, wherein the composite nanomaterial is a composite shell structure of copper-polyphenol nanospheres encapsulating silver nanoparticles (Cu-TA@Ag), and the beacon molecule is a core-shell nanomaterial of 3-mercaptophenylboronic acid (3-MBA).

[0053] Embodiment 2:

[0054] Embodiment 2 of the present application discloses a method for preparing a rapid detection reagent for oil quality.

[0055] The method for preparing a rapid oil quality detection reagent is prepared using the above-mentioned rapid oil quality detection reagent, and comprises the following steps:

[0056] S11, preparation of copper polyphenol nanosol (Cu-TA): 0.2g polyether F127 is dissolved in a mixed solution (containing ethanol, water and ammonia) and stirred, wherein the mixed solution is prepared in the following proportions: 8ml of ethanol, 37ml of ultrapure water, 0.35ml of ammonia solution, and stirred for 1 hour. Then, 5ml of tannic acid (TA) is added to a beaker, and 3.8ml of formaldehyde solution with a mass fraction of 3.7wt% is added to react for 24h, and then 2ml of copper nitrate solution with a solution concentration of 100mg / mL is added; the resulting solution is heated at 100℃ for 12h and then cooled to room temperature, centrifuged at a centrifugal speed of 7000rpm for 10min, and the copper-polyphenol nanosol is obtained by centrifugation.

[0057] In other embodiments, in step S11, the content of each component can also be any value within the following ranges, the mass of the polyether F127 is 0.1-0.3g; the mixed solution is prepared according to the following proportions: the volume of ethanol is 8-10ml, the volume of ultrapure water is 30-50ml, the volume of ammonia solution is 0.1-0.5mL, and the stirring time is 30-60min; the volume of tannic acid (TA) is 4-5mL, the mass fraction of the formaldehyde solution is 3.7wt%, the volume of the formaldehyde solution is 4-5mL, and the reaction time is 12-24h; the concentration of the copper nitrate solution is 80-100mg / mL, the volume of the copper nitrate solution is 1-2mL, the solution heating temperature is 80-100°C, and the heating time is 10-12h; the centrifugal speed is 7000rpm, and the centrifugal time is 10min.

[0058] S12. Preparation of composite nanomaterial (Cu-TA@Ag): After diluting the copper polyphenol nanosol, slowly add the silver ammonia solution to react to obtain a composite nanomaterial.

[0059] In this embodiment, in step S12, the content of each component can be any value within the following range: the volume of the copper polyphenol nanosol after dilution is 30 mL, the addition rate of the silver ammonia solution is 100-300 μL / min, the concentration of the silver ammonia solution is 10-30 mg / mL, the volume of the silver ammonia solution is 10-20 mL, and the solution reaction time is 20-50 min.

[0060] S13. Preparation of a rapid detection reagent for oil quality: Cu-TA@Ag solution and 3-MBA are added to a centrifuge tube and mixed evenly. The centrifuge tube is sealed and incubated at room temperature to obtain a rapid detection reagent for oil quality.

[0061] In this embodiment, in step S13, the content of each component can be any value within the following range: the volume of the composite nanomaterial solution is 0.5-1.5 mL, the volume of the 3-MBA solution is 50-150 μL, the concentration is 0.5-1 mm, the centrifuge tube is 2 mL, and the incubation time is 5-8 h.

[0062] Embodiment three:

[0063] Embodiment 3 of the present application discloses a kit, which comprises the above-mentioned rapid oil quality detection reagent and a methanol solution, wherein the methanol solution is used to extract propyl gallate in the oil.

[0064] Embodiment 4:

[0065] Embodiment 4 of the present application discloses a kit detection method. The kit detection method comprises the following steps:

[0066] S21. Take 2 mL of the above-mentioned kit and 2 mL of the edible oil sample to be tested, add them into a sample bottle, mix them evenly, and treat them with ultrasound for 30 minutes.

[0067] In other embodiments, in step S21, the content of each component may also be any value within the following ranges: the volume of the sample to be tested is 1-2 mL, the volume of the methanol solution is 1-2 mL, and the ultrasonic time is 20-30 min.

[0068] S22. After quantitative extraction of the ultrasonic extract using a 25 mL volumetric bottle, transfer it to a centrifuge tube and centrifuge it at a rate of 5000 rpm for 5 min. Measure it using a Raman spectrometer; measure each sample solution three times and take the average value as the final result.

[0069] In other embodiments, in step S22, the content of each component can also be any value within the following range: the capacity of the centrifuge tube is 10-25 mL, the centrifugal speed is 3000-5000 rpm, and the centrifugal time is 3-5 min; the conditions for the Raman spectrometer measurement are: the laser wavelength is 585-785 nm, the laser power is 30-50 mW, and the signal integration time is 1-5 s.

[0070] Performance Testing:

[0071] Performance Test 1:

[0072] Microscopy, spectroscopy and other techniques were used to observe the morphological and structural changes of the composite nanomaterial (Cu-TA@Ag) in the detection reagent to verify its spectral behavior and clear core-shell structure, and the structure of the prepared nanoparticles was characterized by scanning electron microscopy and transmission electron microscopy.

[0073] Reference Figure 1 In the Cu-TA@Ag nanomaterials prepared by polyphenol reduction method, tannic acid reacts with methanol solution to form catechol nanospheres. 2+ The copper-polyphenol nanosol is formed by chelation with methanol solution. After adding silver ammonia solution, catechol reduces silver ions, and the silver ions are loaded on the copper-polyphenol nanospheres to obtain composite nanomaterials. The presence of catechol reduces the effect of the reducing agent (concentration and reducibility) on the particle size and morphology of silver nanoparticles, and silver nanoparticles with uniform particle size are obtained.

[0074] Reference Figure 2 ,SEM images show that under this concentration of silver ammonia solution, the surface of the Cu-TA sphere is basically surrounded by silver nanoparticles, and they are all spherical and uniform in size.

[0075] Reference Figure 3 ,The transmission electron microscopy images showed that the nanocomposite was composed of Cu-TA spheres inside and surrounded by high-density Ag nanoparticles outside.

[0076] Reference Figure 4 ,From the STEM-EDS element mapping images, it can be seen that the Ag element is distributed on the ,surface of the nanomaterials, verifying the modification by the Ag NPs shell.

[0077] Reference Figure 5 , HRTEM of Ag nanoparticles, the measured interplanar spacing is 0.205nm, corresponding to the Ag(100) plane, to verify the formation of nanoparticles.

[0078] Reference Figure 6 , the selected area electron diffraction (SAED) pattern shows Ag (200), (311), (400) and (511) planes, and multiple diffraction rings centered on the transmission spot indicate that the material is polycrystalline.

[0079] Reference Figure 7 It can be seen that the particle size of the synthesized Cu-TA@Ag is relatively uniform, and most of the Cu-TA@Ag particle sizes are distributed in the range of 200-400nm.

[0080] Reference Figure 8 , according to the zeta potential diagram, the loading of Ag NPs reduced the negative charge of Cu-TA.

[0081] The above results show that Ag nanoparticles are successfully loaded on the surface of Cu-TA spheres, with little effect on the structure of the material. The negative charge system on the surface of Cu-TA@Ag crystals has the advantage of nano-aggregation, which makes the detection signal sensitivity stronger.

[0082] Performance Test 2:

[0083] To verify the structure of the composite nanoparticles and the presence of metals, the materials were tested by FT-IR, XRD, and XPS.

[0084] Reference Fig. 9 From the FT-IR detection diagram, it can be seen that the spectral difference between Cu-TA and Cu-TA@Ag may be caused by charge transfer or local electric field. The FT-IR peak of Cu-TA and Cu-TA@Ag is 1750cm -1 、1420cm -1 、3100cm -1 These are characteristic absorption peaks of tannic acid.

[0085] Reference Fig.10 In the XRD patterns of Cu-TA and Cu-TA@Ag, the three diffraction peaks at 43.3°, 50.4°, and 74.1° at 2θ are consistent with the (111), (200), and (220) crystal planes of copper, and the four diffraction peaks at 38.1°, 44.2°, 64.4°, and 77.3° at 2θ are consistent with the (111), (200), and (220) crystal planes of silver. This indicates that the structure of the synthesized composite material is copper-polyphenol nanospheres encapsulating silver nanoparticles. The silver nanoparticles introduce localized surface plasmon resonance (LSPR) to enhance the Raman signal, and the presence of silver can also enhance the nanozyme activity of the material. This composite material is used as the Raman basis, and 3-MBA containing boric acid groups is used as a beacon molecule to achieve the detection of oil products.

[0086] Performance Test 3:

[0087] Characterization Different nanomaterials (metals, metal oxides, etc.) have different intrinsic physicochemical behaviors and therefore exhibit different intrinsic enzyme-like catalytic activities. Therefore, this example conducts a typical color reaction to study the activity of Cu-TA@Ag nanomaterials. 2,2-naphthalenenitride-(3-ethylbenzothiazole-6-sulfonic acid) acid ammonium salt (ABTS) has higher sensitivity and accuracy, is easily oxidized and discolored by free radicals, and has a clear absorption peak in the visible light region.

[0088] Reference Fig.11 , the color development of ABTS is mediated by the redox mixture of ABTS, Cu-TA@Ag and H2O2. After ABTS oxidation, ABTS· +There is obvious absorption in the visible light region (420, 615, 732nm). Therefore, the UV-visible spectrum scanning on the Cu-TA@Ag / H2O2 / ABTS system proves that Cu-TA@Ag has the ability to convert ABTS into ABTS· + of nanozyme activity.

[0089] Reference Fig.12 ,When ABTS / H2O2 / Cu-TA@Ag exists, the absorbance at 420nm is significantly higher than that of ABTS / Cu-TA@Ag and H2O2 / Cu-TA@Ag, indicating that the presence of Cu-TA@Ag can promote the oxidation of ABTS.

[0090] Reference Fig.13 , in the system containing ABTS, the material can promote the decomposition of H2O2 and generate free radicals, and the oxygen-related free radicals in the Cu-TA@Ag-H2O2 system were determined by electron paramagnetic resonance (EPR).

[0091] Reference Fig.14 and Fig.15 5,5-dimethylpyridine n-oxide (DMPO) and 2,2,6,6-tetramethylpyridine (TEMP) were used as free radical scavengers. DMPO can capture extremely short-lived free radicals and O2 - Free radicals, forming DMPO-·OH and DMPO-O2· - DMPO-·OH、DMPO-O2· - The paramagnetic characteristic peak areas are 1:2:2:1 and 1:1:1:1 respectively. TEMP can be used with 1 O2 combines to form TEMP- 1 O2, characteristic peak area is 1:1:1.

[0092] In summary, the Cu-TA@Ag prepared by this method has the ability to convert ABTS into ABTS· + The nanozyme activity was confirmed, which verified that the oil detection reagent prepared by this method has good nanozyme activity.

[0093] Performance Test 4:

[0094] To verify the recognition ability of Cu-TA@Ag and 3-MBA, 3-MBA was mixed with Cu-TA@Ag and then the Raman signal intensity test was performed.

[0095] Reference Fig.16 The results show that the signal molecule forms an Ag-S bond in the form of sulfate, and 3-MBA can be modified on Cu-TA@Ag. In the SERS spectrum, the -1The vibration mode of the completely symmetrical benzene ring (8a) in 3-MBA is observed, and after propyl gallate is added to the system, the boric acid structure in 3-MBA combines with the catechol structure in propyl gallate, so that the vibration mode of the original completely symmetrical benzene ring of 3-MBA is changed to the incomplete symmetrical vibration mode of the benzene ring, resulting in a change in the Raman signal. The charge transfer effect of the mercapto conjugated benzene in 3-MBA produces additional chemical enhancement, providing a repeatable SERS signal, thereby better shielding the noise in the medium. Therefore, the Raman substrate of this embodiment not only has a good enhancement factor, but also has stability and repeatability, and propyl gallate can be indirectly detected by the Raman substrate.

[0096] Performance Test 5:

[0097] Verify the quantitative analysis and sensitivity of the method of the present invention.

[0098] Reference Fig.17 Under the conditions of reaction temperature of 25°C, reaction time of 20 min and reaction volume of 150 μL, the SERS response of Cu-TA@Ag substrate to PG concentration was obtained. The SERS internal standard peak is 662 cm -1 PG stock solution with an initial concentration of 10 mM was prepared using anhydrous PG powder, and then diluted to different concentrations with ultrapure water for experiments. Under the same conditions, as the PG concentration decreased, the internal standard peak intensity without Raman signal remained unchanged (1571 cm -1 、1074cm -1 、1022cm -1 、998cm -1 ) showed a downward trend, and the combination of PG and 3-MBA showed a downward trend, indicating that the peak value of the Raman signal was closely related to the PG concentration, indicating that the Raman substrate can be used to indirectly detect PG, and this performance is crucial for the determination and identification of oil quality.

[0099] Performance Test 6:

[0100] The feasibility of the method of the present invention was evaluated.

[0101] Reference Fig.18 , at 1571cm -1 In the change of Raman peak intensity, the linear fitting correlation coefficient (R2=0.9967) is linear, indicating that the Raman substrate can indirectly detect PG, the minimum detection limit of the method is 3.8nm, and the detection range is 0.01-100μm. Therefore, the method of the present invention has good selectivity for rapid sensing of propyl gallate.

[0102] Performance Test 7:

[0103] The reproducibility of the method was tested to ensure that the nanomaterials can be used in practical applications.

[0104] Under the same conditions, 10 groups of propyl gallate solutions (1 μm) were randomly measured, referring to Fig.19 The relative standard deviation (RSD) after data processing is 2.05%, indicating that this method has high reproducibility and homogeneity. It can solve the problem of low SERS reproducibility, meet the requirements of quantitative analysis, and is suitable for real-time analysis of oil samples.

[0105] Performance Test 8:

[0106] To verify the change in the SERS intensity of the material to propyl gallate after long-term storage of the reagent of the present invention, the material was stored at 4° C. and measured regularly to obtain the Raman spectrum of the Raman substrate to PG.

[0107] Reference Fig. 20 , indicating that with the extension of time, the Raman intensity decreased slightly but not significantly, and the RSD was only 1.01%, indicating that the detection reagent has good long-term storage stability.

[0108] Performance Test 9:

[0109] To study the specificity of the reagent in SERS detection, this test selected some common metal ions (K + 、Na + , Cu 2 + , Ca 2+ Mg 2+ ) and other antioxidants (BHT, TBHQ, BHA) were used as interferents in the experiment.

[0110] Reference Fig.21 Compared with the signal enhancement after adding propyl gallate, the addition of interference term has an effect on the wavelength of 1571cm -1 The signal at the position is not greatly affected, and the interference intensity tends to be consistent and close to the blank sample, indicating that the Cu-TA@Ag Raman substrate has Raman sensing specificity for propyl gallate.

[0111] Performance Test 10:

[0112] Based on the practical application of the present invention, the detection ability of Cu-TA@Ag(3-MBA) for propyl gallate in actual food samples was tested, and its applicability in complex substrates was studied. The three actual samples of peanut oil, sesame oil and sesame oil in the canteen were detected by the labeled recovery method. As shown in Table 1, after the food samples were extracted with methanol, the Raman intensity of the samples was measured, and the concentration and recovery rate of propyl gallate in the food were calculated.

[0113] Table 1:

[0114]

[0115]

[0116] According to Table 1, the recoveries of peanut oil, sesame oil and sesame oil were 95.5-101.6%, 90.8-98.5% and 92.9-102.6%, respectively. The RSD values ​​of propyl gallate in peanut oil, sesame oil and sesame oil were between 1.11% and 3.79%, and the lowest RSD value was 1.11%, which confirmed the accuracy of the method and showed that the synthesized Raman substrate can be used for the detection of propyl gallate in actual samples. In short, the material does not require complex pretreatment and large instruments. The concentration of propyl gallate in food can be detected by a simple detection method, which provides an excellent rapid detection reagent for uniform detection of antioxidant propyl gallate in oil products.

[0117] The invention synthesizes a composite material of copper-polyphenol nanospheres coated with silver nanoparticles, uses the composite material as a Raman substrate, and uses 3-MBA containing a boric acid group as a beacon molecule to obtain a rapid detection reagent. When the antioxidant propyl gallate in the oil product is combined with the rapid detection reagent of the invention, the Raman signal is enhanced, thereby realizing rapid trace detection of the oil product quality. Provided is a rapid detection reagent and a detection method for propyl gallate in oil products that is accurate, rapid, and easy to promote and use.

[0118] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A rapid detection reagent for oil quality, characterized in that: The invention comprises a composite nano material and a beacon molecule. The composite nano material is a composite material shell structure of copper-polyphenol nanospheres encapsulating silver nano particles (Cu-TA@Ag), and the beacon molecule is a core-shell nano material of 3-mercaptophenylboronic acid (3-MBA).

2. A method for preparing a rapid detection reagent for oil quality, characterized in that: The rapid detection reagent for oil quality as claimed in claim 1 is used for preparation, comprising the following steps: S11, preparation of copper polyphenol nanosol (Cu-TA): polyether F127 is dissolved in a mixed solution (containing ethanol, water and ammonia), stirred, and then tannic acid (TA) is added, and then formaldehyde solution is added for reaction, and then copper nitrate solution is added; the obtained solution is heated and then cooled to room temperature, and centrifuged to obtain copper-polyphenol nanosol; S12, preparation of composite nanomaterial (Cu-TA@Ag): after diluting the copper polyphenol nanosol, slowly adding the silver ammonia solution to react to obtain a composite nanomaterial; S13. Preparation of a rapid detection reagent for oil quality: Cu-TA@Ag solution and 3-MBA are added to a centrifuge tube and mixed evenly. The centrifuge tube is sealed and incubated at room temperature to obtain a rapid detection reagent for oil quality.

3. The method for preparing a rapid detection reagent for oil quality according to claim 2, characterized in that: In step S11: the mass of the polyether F127 is 0.1-0.3g; the mixed solution is prepared according to the following proportions: the volume of ethanol is 8-10ml, the volume of ultrapure water is 30-50ml, the volume of ammonia solution is 0.1-0.5mL, and the stirring time is 30-60min; the volume of tannic acid (TA) is 4-5mL, the mass fraction of the formaldehyde solution is 3.7wt%, the volume of the formaldehyde solution is 4-5mL, and the reaction time is 12-24h; the concentration of the copper nitrate solution is 80-100mg / mL, the volume of the copper nitrate solution is 1-2mL, the solution heating temperature is 80-100°C, and the heating time is 10-12h; the centrifugal speed is 7000rpm, and the centrifugal time is 10min.

4. The method for preparing a rapid detection reagent for oil quality according to claim 2, characterized in that: In step S12, the volume of the copper polyphenol nanosol after dilution is 30 mL, the silver ammonia solution is added at a rate of 100 to 300 μL / min, the concentration of the silver ammonia solution is 10 to 30 mg / mL, the volume of the silver ammonia solution is 10 to 20 mL, and the solution reaction time is 20 to 50 min.

5. The method for preparing a rapid detection reagent for oil quality according to claim 2, characterized in that: In step S13, the volume of the composite nanomaterial solution is 0.5-1.5 mL, the volume of the 3-MBA solution is 50-150 μL, the concentration is 0.5-1 mm, the centrifuge tube is 2 mL, and the incubation time is 5-8 h.

6. A kit, characterized in that: The invention comprises the rapid detection reagent for oil quality as claimed in claim 1 and a methanol solution, wherein the methanol solution is used for extracting propyl gallate in the oil.

7. A kit detection method, characterized in that: The following steps are involved: S21, mixing the kit as claimed in claim 6 and the sample to be tested uniformly, and ultrasonically treating; S22. Quantitatively transfer the extract after ultrasonication to a centrifuge tube for centrifugation, and measure it using a Raman spectrometer; measure each sample solution three times and take the average value.

8. A kit detection method according to claim 7, characterized in that: In step S21: the volume of the sample to be tested is 1-2 mL, the volume of the methanol solution is 1-2 mL, and the ultrasonic time is 20-30 min.

9. A kit detection method according to claim 7, characterized in that: In step S22: the capacity of the centrifuge tube is 10-25 mL, the centrifugal speed is 3000-5000 rpm, and the centrifugal time is 3-5 min.

10. A kit detection method according to claim 7, characterized in that: In step S22, the Raman spectrometer measurement conditions are: laser wavelength is 585-785 nm, laser power is 30-50 mW, and signal integration time is 1-5 s.

Citation Information

Patent Citations

  • Gold nano probe for detecting benzoyl peroxide as well as preparation method and application thereof

    CN110280755A

  • Rapid detection reagent and detection method for formaldehyde in beer

    CN110879223A

  • Five-metal nano-enzyme as well as preparation method and application thereof

    CN116966916A

  • Colorimetric-SERS dual-mode detection and photo-thermal sterilization method for specific detection of vibrio parahaemolyticus and application of colorimetric-SERS dual-mode detection and photo-thermal sterilization method

    CN117169190A

  • Ginkgolic acid rapid detection method based on tannic acid copper gold nano enzyme

    CN117451702A